ANALISIS PENGARUH KONTRIBUSI PAJAK KENDARAAN BERMOTOR DAN BEA BALIK NAMA KENDARAAN BERMOTOR TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI PROVINSI KALIMANTAN SELATAN TAHUN 2003-2012 - Ruslinda Agustina; Rina Arliani (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2015)
Abstract, This research aimed to examine the effect of the contribution of the PKB and BBNKB to PAD in South Kalimantan province in 2003-2012. The method used quantitative methods, namely measurement of objective statistical data and through SPPS version 16. The results of the test or test the hypothesis partially explains PKB t affect the PAD, while BBNKB no effect on the South Kalimantan provincial PAD period 2003-2012. The results of hypothesis testing simultaneously or PKB and BBNKB F test against provincial PAD bepengaruh South Kalimantan period 2003-2012. the results of the regression estimates indicate that there are two independent variables in the regression model is able to explain 64% of the revenue and the balance of 36% is explained by other variables not included in this study.